2015
DOI: 10.1038/ng.3287
|View full text |Cite
|
Sign up to set email alerts
|

A germline homozygous mutation in the base-excision repair gene NTHL1 causes adenomatous polyposis and colorectal cancer

Abstract: The genetic cause underlying the development of multiple colonic adenomas, the premalignant precursors of colorectal cancer (CRC), frequently remains unresolved in patients with adenomatous polyposis. Here we applied whole-exome sequencing to 51 individuals with multiple colonic adenomas from 48 families. In seven affected individuals from three unrelated families, we identified a homozygous germline nonsense mutation in the base-excision repair (BER) gene NTHL1. This mutation was exclusively found in a hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
283
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(312 citation statements)
references
References 21 publications
18
283
0
4
Order By: Relevance
“…However, up to 50% of LLS CRC exhibits biallelic somatic inactivation of DNA MMR genes within the tumor (Geurts-Giele et al, 2014;Haraldsdottir et al, 2014;Kang et al, 2015;Rodriguez-Soler et al, 2013;Sourrouille et al, 2013). It has now been demonstrated that many of these are due to constitutional mutations and epimutations in other genes, including POLD1 and POLE (Haraldsdottir et al, 2014;Palles et al, 2013), MUTYH (Castillejo et al, 2014;Syngal et al, 2015), FAN1 (Segui et al, 2015), NTHL1 (Weren et al, 2015), PIK3CA (Cohen et al, 2016), BRCA1/2, 2 PTEN, STK11 (Yurgelun et al, 2015) and other cancer susceptibility genes (SMAD4, BMPR1A, KLLN, AKT1, AXIN2, BUB1 and BUB3) (Hansen et al, 2017) with some resultant tumours sometimes acquiring two somatic mutations in the same MMR gene, and consequently dMMR and/or MSI (Frayling and Arends, 2015;Short et al, 2015). Biallelic MSH3 mutations have also been identified as predisposing to MSI CRC, however this occurs in longer repeats than is currently investigated by conventional MSI testing.…”
Section: "Lynch-like Syndrome" and Novel Aetiologies Of Msi Colorectamentioning
confidence: 99%
See 1 more Smart Citation
“…However, up to 50% of LLS CRC exhibits biallelic somatic inactivation of DNA MMR genes within the tumor (Geurts-Giele et al, 2014;Haraldsdottir et al, 2014;Kang et al, 2015;Rodriguez-Soler et al, 2013;Sourrouille et al, 2013). It has now been demonstrated that many of these are due to constitutional mutations and epimutations in other genes, including POLD1 and POLE (Haraldsdottir et al, 2014;Palles et al, 2013), MUTYH (Castillejo et al, 2014;Syngal et al, 2015), FAN1 (Segui et al, 2015), NTHL1 (Weren et al, 2015), PIK3CA (Cohen et al, 2016), BRCA1/2, 2 PTEN, STK11 (Yurgelun et al, 2015) and other cancer susceptibility genes (SMAD4, BMPR1A, KLLN, AKT1, AXIN2, BUB1 and BUB3) (Hansen et al, 2017) with some resultant tumours sometimes acquiring two somatic mutations in the same MMR gene, and consequently dMMR and/or MSI (Frayling and Arends, 2015;Short et al, 2015). Biallelic MSH3 mutations have also been identified as predisposing to MSI CRC, however this occurs in longer repeats than is currently investigated by conventional MSI testing.…”
Section: "Lynch-like Syndrome" and Novel Aetiologies Of Msi Colorectamentioning
confidence: 99%
“…For example NGS approaches has helped identify suspected LLS patients that actually have Lynch syndrome, as some tumours may be due to constitutional mutations in DNA MMR genes that are not detectable by standard testing (Rodriguez-Soler et al, 2013). NGS testing has also identified somatic mutations coupled with LOH (Geurts-Giele et al, 2014;Haraldsdottir et al, 2014;Kang et al, 2015;Rodriguez-Soler et al, 2013;Sourrouille et al, 2013) and constitutional mutations in additional genes as causes of dMMR (Adam et al, 2016;Castillejo et al, 2014;Cohen et al, 2016;Haraldsdottir et al, 2014;Palles et al, 2013;Segui et al, 2015;Syngal et al, 2015;Weren et al, 2015).…”
Section: The Role Of Next Generation Sequencing In Determining Mmr Stmentioning
confidence: 99%
“…In families or simplex cases with hereditary cancer syndromes identification of new tumor suppressor genes or inactivating mutations in existing genes is most often the case (Gylfe et al, 2013; Smith et al, 2013; Gala et al, 2014; Nieminen et al, 2014; Segui et al, 2015; Weren et al, 2015). In our study an activating 16 kb duplication was found upstream of GREM1 .…”
Section: Discussionmentioning
confidence: 99%
“…Exome studies have also recently identified high penetrant mutations in new CRC predisposing genes e.g. the NTHL1 gene with a recessive inheritance of the phenotype, predisposing to BER associated adenomatous polyposis and CRC (Weren et al, 2015). However, in the attenuated and mixed polyposis syndromes only a fraction of the disease‐causing mutations can still be identified (Fodde et al, 1992; Miyoshi et al, 1992; Lynch et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The main differential diagnoses for APC-related adenomatous polyposis are recessive conditions, especially MUTYH polyposis (24), and also MSH3-and NTHL1-associated disorders (25,26), although these are unlikely to present in childhood.…”
Section: Geneticsmentioning
confidence: 99%